1980
DOI: 10.3168/jds.s0022-0302(80)82972-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Lactating Cows to Gossypol from Cottonseed Meal Rations

Abstract: We evaluated the potential for gossypol intoxication and resulting effects of feeding large amounts of cottonseed meal to dairy cows in early lactation. Twenty-four Holstein cows were grouped by age, prior production, and days postpartum and randomly assigned to one of three diets. After 14-day standardization cows individually were fed a blended corn-corn silage ration supplemented with screw-pressed cottonseed meal, direct solvent extracted cottonseed meal, or soybean meal during a 14-wk comparison. Packed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
1
8

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 18 publications
8
50
1
8
Order By: Relevance
“…However, there is evidence showing that part of gossypol escapes ruminal fermentation (Mena et al, 2004) and can affect animal health and performance (Risco et al, 2002). Effects of gossypol can lead to low hemoglobin and hematocrit levels (Velasquez-Pereira et al, 1999), osmotic fragility of erythrocyte, decrease in cell antioxidant power (Risco et al, 2002), productive performance (Santos et al, 2003;Villaseñor et al, 2008), milk production and breathing rate and finally death (Lindsey et al, 1980). Some authors suggest that cottonseed can be used in milking cows at up to 3-4 kg cow −1 d −1 or 150 g kg −1 of their diet without negative effects (Coppock et al, 1987;Arieli, 1998;Zhang et al, 2007), although gossypol concentrations are different depending on the cotton varieties (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence showing that part of gossypol escapes ruminal fermentation (Mena et al, 2004) and can affect animal health and performance (Risco et al, 2002). Effects of gossypol can lead to low hemoglobin and hematocrit levels (Velasquez-Pereira et al, 1999), osmotic fragility of erythrocyte, decrease in cell antioxidant power (Risco et al, 2002), productive performance (Santos et al, 2003;Villaseñor et al, 2008), milk production and breathing rate and finally death (Lindsey et al, 1980). Some authors suggest that cottonseed can be used in milking cows at up to 3-4 kg cow −1 d −1 or 150 g kg −1 of their diet without negative effects (Coppock et al, 1987;Arieli, 1998;Zhang et al, 2007), although gossypol concentrations are different depending on the cotton varieties (Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, cottonseed meal is used widely as a protein supplement in the diets of cattle and sheep but not of young calves whose rumen are not yet fully functioning (Adams et al, 1960). A recent study, however, has reported that feeding of large amounts of cottonseed meal to dairy cows in early lactation can be toxic (Lindsey et al, 1980). In this study cows were given cottonseed meal rations containing 6.6 and 42.7 mg of free gossypol kg-I body weight day-I for 14 weeks.…”
Section: Toxicity To Ruminant Animalsmentioning
confidence: 99%
“…In 1975, gossypol toxicity developed (in a 700 cow dairy herd in Alabama) when large amounts of cottonseed meal were fed as the single source of protein to achieve high levels of milk production, resulting in the death of 25 mature cows. Lindsey et al (7) reported gossypol intoxication in mature dairy cattle consuming direct solvent extracted cottonseed meal containing high free gossypol. This research accompanied by periodic rediscoveries of gossypol poisoning in cattle (8; 9; 10; 11; 12; 13; 14) and in sheep (15; 16; 17) renewed concerns about the safety of feedstuffs containing gossypol.…”
Section: Mechanically Processed Cottonseed 181mentioning
confidence: 98%